Metaverse-based virtual reality experience and endurance performance in sports economy: Mediating role of mental health and performance anxiety - Huang, Zengsong; Choi, Deok-Hwan; Lai, Bingsen; Lu, Zhicheng; Tian, Haijun (Frontiers in Public Health, 2022)
Metaverse sports arena is gaining popularity globally that empowers virtual reality sporting experience through digital avatars. The main objective of the current study is to explore the impact of the Metaverse-based virtual reality sporting experience on the endurance performance of young Chinese athletes, with the mediating role of their mental health condition and performance anxiety. The study's participants mainly included Chinese athletes, especially the sample group is an accurate depiction of young athletes using a convenience sampling approach. SEM-AMOS statistical software was used for the analysis and validation of the proposed relationships. The study findings statistically validate that mental health and performance anxiety fully mediate the direct associations between virtual reality sporting experiences and the endurance performance of young Chinese athletes. Interestingly, the mental health condition of the young Chinese athletes imposes a greater impact on their endurance performance, in contrast to the adverse effects of their performance anxiety. The outcomes of the present research guide young athletes on the opportunities to enhance their virtual reality sporting abilities and boost their endurance performance. Policymakers can also build systems to dissolve physical and geographical barriers, reduce performance anxiety, and sustain mental health in virtual reality sporting events through the metaverse.